Letter from Jesse M. Unruh - Jesse M. Unruh::::::
This letter from the California Democratic Delegation, chaired by Jesse M. Unruh, urges delegates to support a coordinated slate of candidates for party leadership at meetings held August 10–11 in Sacramento. It argues that the Democratic Party faces significant political challenges in California, including narrow legislative margins and competitive statewide and presidential races, making strong unified leadership essential. The endorsed candidates pledge to work collaboratively, establish joint northern and southern headquarters, coordinate fundraising, and strengthen party organization. The letter lists recommended candidates for Democratic National Committeeman and Committeewoman as well as multiple state party offices. It concludes that building an effective, unified party structure is necessary to secure Democratic victories now and in the future, and is signed by numerous prominent Democratic leaders.